Development of sodium-MRI for stroke and tumour investigations in rodents - Wetterling, Friedrich (Springer, 2008)
The aim of this research was to develop a technique for accurately detecting and quantifying the concentration of sodium in diseased tissue via MRI. Measures of tissue sodium concentration can pro- vide information regarding the viability of tissue, thereby aiding in the early detection of disease and in the development and moni- toring of therapeutic interventions (1, 2). However, 23Na-MRI is hindered by a signal approximately 100,000 times less than that of conventional 1H-MRI and very short in vivo T2 relaxation times (*1–2 ms). Consequently, it is necessary to develop specialised hardware and imaging pulse sequence solutions to produce images of adequate quality
IRISH JOURNAL OF MEDICAL SCIENCE
Faculty of Radiologists Royal College of Surgeons in Ireland